PENGARUH ANTARA LABA BERSIH, TOTAL ARUS KAS, ROE, PER DAN EPS TERHADAP RETURN SAHAM (Studi Empiris terhadap 22 perusahaan consumer goods yang terdaftar pada Bursa Efek Indonesia 2007 – 2010) - Arief Sugiono; Andrianto Andrianto (Universitas Bunda Mulia, 2017)
This research aimed to determine the effect of net income, total cash flow, ROE, PER and EPS simultaneously or partial, as well as to determine which variable is more dominant influence on stock return consumer services company listed on the Indonesia Stock Exchange (BEI) in the period 2007 – 2010. Samples taken by 22 consumer Services Company listed on the Stock Exchange during the years of observation 2007-2010. Then for the company that owns the data is not normal, is not used in this study. The process of data analysis the first is data analysis, where the author observed and compared between the movement of net income, total cash flow, ROE, PER and EPS by the movement of stock returns each year. Then to obtain more definitive results, the authors performed statistical tests.The results of data analysis and statistical tests manually obtained that simultaneous net income, total cash flow, ROE, PER and EPS had no effect on stock returns consumer services company listed on the Stock Exchange. But in testing the partially obtained that the ratio ROE is the only financial ratios that affect the stock returns of consumption services company listed on the Stock Exchange the period 2007-2010.Keywords: Net Income, Cash Flow, ROE, EPS, PER